2018
DOI: 10.1186/s12859-018-2175-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on multi-omic oscillations in Escherichia coli metabolic networks

Abstract: BackgroundTwo important challenges in the analysis of molecular biology information are data (multi-omic information) integration and the detection of patterns across large scale molecular networks and sequences. They are are actually coupled beause the integration of omic information may provide better means to detect multi-omic patterns that could reveal multi-scale or emerging properties at the phenotype levels.ResultsHere we address the problem of integrating various types of molecular information (a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In this paper, the investigators demonstrated the capability of COSMOS to integrate PPI, GRN and two different metabolic networks from transcriptomics, phosphoproteomics, and metabolomics data in clear cell renal cell carcinoma. Similar non-matrix-based omics methods were used in bacteria such as the MORA approach, which integrates various layers of omics data (transcriptomic, proteomics, metabolomics, genomics) to identify the affected pathways ( Bardozzo et al, 2018 ). This method used mutual synchronisation of binarised omics measurements rather than a matrix deconvolution approach to identify affected pathways.…”
Section: Future Challenges and Potential Mitigating Strategies To Develop Network Biology Approaches For Precision Medicinementioning
confidence: 99%
“…In this paper, the investigators demonstrated the capability of COSMOS to integrate PPI, GRN and two different metabolic networks from transcriptomics, phosphoproteomics, and metabolomics data in clear cell renal cell carcinoma. Similar non-matrix-based omics methods were used in bacteria such as the MORA approach, which integrates various layers of omics data (transcriptomic, proteomics, metabolomics, genomics) to identify the affected pathways ( Bardozzo et al, 2018 ). This method used mutual synchronisation of binarised omics measurements rather than a matrix deconvolution approach to identify affected pathways.…”
Section: Future Challenges and Potential Mitigating Strategies To Develop Network Biology Approaches For Precision Medicinementioning
confidence: 99%
“…However, studies of astrocyte metabolism in association with lipotoxicity and tibolone treatment have focused on deciphering specific elements through experimental simulation, ignoring mechanisms that can occur at multiple levels of biological organization (omics) and creating a lack of understanding on the metabolic relationship between these interactions and pathological conditions (Ravindran et al, 2019). In this aspect, with the increase and availability of large-scale multi-omic data, there is a huge potential on the biological insights that can be drawn from integrating these data (Currais et al, 2015) as it has been done for other organisms in the study of response to changing environment conditions (Bardozzo et al, 2018). Therefore, developing a comprehensive view of the mechanisms implicated in brain behavior involves systemic approaches, which can be evaluated through mathematical representations of metabolism, such as genome-scale metabolic networks (GEMs) (Basler and Nikoloski 2011;Nielsen 2017).…”
Section: Introductionmentioning
confidence: 99%
“…At several level, the traditional approaches are embedded in DL models showing a fair balance between accuracy, generalization power and computational time costs [6]- [9]. After all, the images are a matrix of values, thus enabling researchers to use binarization in complex networks [10], Bayesian networks [11] and biological networks/pathways [12]. Even if there are several binarization techniques in literature, none is the gold standard.…”
Section: Introductionmentioning
confidence: 99%

Adaptive binarization based on fuzzy integrals

Bardozzo,
De La Osa,
Horanska
et al. 2020
Preprint
Self Cite